CODE MIXING USED BY THE TEACHERS OF LPAM ENGLISH COURSE - Okti Wilymafidini (Politeknik Negeri Bengkalis, 2021)
This research discuss about Code Mixing Used by Teacher of LPAM English Course in the Teaching Learning process. This research aims to Â find out the type of code-mixing, and the reason of using code-mixing. The theory used is Hoffmanâ€Ÿs theory about Code Mixing. The data were analyzed using descriptive method. The researcher used observation and interview as the instruments to find out the data. The findings showed that there were three types of code-mixing used by the teachers, they were Intra Sentential Code-Mixing, intra lexical code mixing and Involving Change of Pronunciation, and the reason of using code-mixing were Quoting Somebody Else, Interjection, Repetition Used for Clarification and Real Lexical Need. Â